Revisit Intention Obyek Wisata Pantai Krapyak Kabupaten Pangandaran: Pengaruh Citra Destinasi Wisata, Pengalaman Wisatawan dan Media sosial - Andhi Johan Suzana; Tri Esti Masita; Herlina Tiara Alvani (FEB UNWIKU PURWOKERTO, 2022)
The purpose of this study was to determine the effect of the image of a tourist destination, tourist experience and social media on the intention to return to the karapyak beach tourist attraction in Pangandaran Regency. The sampling technique used in this study was non-probability sampling using purposive sampling method. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis, it shows that the image of a tourist destination and social media has a significant positive effect on the intention to return, while the tourist experience has no effect on the intention to return. The implications of this research are that the local government is expected to pay attention to the procurement of certain events to increase the interest in visiting tourists again, such as holding annual events such as New Year's Eve, sea alms, kite festivals and so on. In addition, it is necessary to carry out continuous evaluations or follow-ups every year, so that tourist objects remain known to the wider community and become the main alternative choice in traveling..